Theoretical and methodological foundations of forming of students’ communicative skills while learning psychological and pedagogical disciplines (Pedagogy of Higher and Secondary Education, 2013)
Maksymenko I. G., Shepelenko T. L. Theoretical and methodological foundations of forming of students’ communicative skills while learning psychological and pedagogical disciplines.The article substantiates the nature, content, structure of communicative skills. It also defines theoretical and methodological principles of their formation while learning psychological and pedagogical disciplines.
Keywords: skills; communicative skill; theoretical and methodological foundations